The Effectiveness of Web-Based Teaching Materials in Mandarin Subject - Zhu, Mega; Siahaan, Sardianto Markos; Somakim, Somakim (Universitas Negeri Malang, 2022)
This study aimed to determine the effectiveness of web-based teaching materials about